Pengembangan Potensi Wisata Hiking Di Curug Cikawah, Desa Ciasmara Kabupaten Bogor - Abidin, Jenal; Yunus, Farhan Rahadian; Christine, Novia (Politeknik Pariwisata Medan, 2024)
This research discusses the development of hiking tourism potential at Curug Cikawah, Ciasmara Village, Bogor Regency. With the growing trend of special interest tourism, the development of hiking tourism in the area is expected to provide a variety of tourist attractions and have a positive impact on the economy of the local community. This research uses a qualitative descriptive approach with observation, interviews, documentation and SWOT analysis methods. The results of the SWOT analysis show strengths such as a beautiful atmosphere and local guides, weaknesses such as locations far from the crowds, opportunities such as sports tourism trends, and threats that need to be anticipated. The strategy for developing hiking tourism at Curug Cikawah was also prepared based on the results of the SWOT analysis. It is hoped that the development of hiking tourism can provide benefits for developers, local communities and tourists visiting the area.